Effects of oregano (Origanum vulgare L.) and rosemary (Rosmarinus officinalis L.) aqueous extracts on broiler performance, immune function and intestinal microbial population. Issue 1 (1st January 2016) - Franciosini, Maria Pia; Casagrande-Proietti, Patrizia; Forte, Claudio; Beghelli, Daniela; Acuti, Gabriele; Zanichelli, Dario; dal Bosco, Alessandro; Castellini, Cesare; Trabalza-Marinucci, Massimo
ABSTRACT: A 57-day study was performed to determine the effects of two aqueous extracts (AEs) on broiler performance, immune function and intestinal microflora. Four groups of 75 one-day-old female broilers (Ross308) received one of the following treatments: (1) a standard commercial feed (C); (2) C supplemented with 2 g/kg rosemary AE (R); (3) C supplemented with 2 g/kg oregano AE (O); (4) C supplemented with 1 g/kg oregano AE + 1 g/kg rosemary AE (OR). Individual body weight, average daily gain, average daily feed intake and feed conversion efficiency were determined at 1, 11, 22, 36 and 57 days. Sample collections for IgG titration and intestinal microflora examination were performed at 22 and 57 days. The addition of oregano AE alone or in combination with rosemary AEs improved body weight up to 36 days of age ( P  < .01). A time effect was recorded for total serum IgG in all groups ( P  < .001) and the percentage increase of the value was positively ( P  < .05) influenced by the AE supplementation. Lactobacilli raised ( P  < .001) in ileum and cecum of all groups supplemented with AEs. Staphylococcus spp . population was constantly lower in both intestinal tracts of the AE supplemented groups. On the basis of our results, AEs could improve broiler performance and immune function and contribute to a balanced gut microflora, essential for the digestion process and protection against enteropathogenic organisms.